2013
DOI: 10.3329/pa.v18i2.17460
|View full text |Cite
|
Sign up to set email alerts
|

Soil Flooding Tolerance in Lentil at Vegetative Stage

Abstract: The experiment compared the relative tolerance of some advanced lines and a variety of lentil viz. BD3859, BD3905, BD3867, ILL5087, ILL5133 and BINAmasur1 (variety) to soil flooding. The growth rates of the genotypes considerably reduced when flooding imposed at vegetative stage. However, the genotypes responded differently to flooding onward during recovery period. Leaf and roots showed highly vulnerable to flooding. Flooding promoted extensive leaf senescence and desiccation. Flooding induced damaging of roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Filtering criteria applied (bad drainage soils and humid sites according to the annual De Martonne aridity index) are in line with the main factors favoring waterlogging that affects lentil-type of soil and precipitation (Lake and Sadras, 2019). The low proportion of selected populations could agree with the high sensitivity of lentil to waterlogging in any of the vital stages, especially at the germination and vegetative stages Nessa et al, 2007;Materne and Siddique, 2009;Malik et al, 2015), which would also be present in most of its wild relatives. A previous study on waterlogging tolerance carried out by Wiraguna et al (2017) with cultivated accessions of lentils from major lentil-producing countries with different climates, found that only those from Bangladesh showed waterlogging tolerance at the germination stage.…”
Section: Environmental Filtering Method-abiotic Stress Analysesmentioning
confidence: 71%
“…Filtering criteria applied (bad drainage soils and humid sites according to the annual De Martonne aridity index) are in line with the main factors favoring waterlogging that affects lentil-type of soil and precipitation (Lake and Sadras, 2019). The low proportion of selected populations could agree with the high sensitivity of lentil to waterlogging in any of the vital stages, especially at the germination and vegetative stages Nessa et al, 2007;Materne and Siddique, 2009;Malik et al, 2015), which would also be present in most of its wild relatives. A previous study on waterlogging tolerance carried out by Wiraguna et al (2017) with cultivated accessions of lentils from major lentil-producing countries with different climates, found that only those from Bangladesh showed waterlogging tolerance at the germination stage.…”
Section: Environmental Filtering Method-abiotic Stress Analysesmentioning
confidence: 71%